Pengaruh Brand Love dan Kualitas Pelayanan terhadap Kepuasan Pelanggan pada Jasa Pengiriman (Studi Kasus Spx Express di Singaparna) - Silvi Nurzamil; Aditia Abdurachman (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This research is intended to analyze the influence of Brand Love and Service Quality on Customer Satisfaction within the logistics service industry. The study adopts a quantitative research design by applying the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach, involving a total of 100 respondents as the research sample. The findings demonstrate that all measurement indicators satisfy the requirements of validity and reliability, as reflected by Average Variance Extracted (AVE) values above 0.50 and Composite Reliability values exceeding 0.70. Furthermore, the coefficient of determination (R-square) value of 0.700 indicates that Brand Love and Service Quality collectively account for 70% of the variation in Customer Satisfaction. The results of hypothesis testing confirm that Brand Love exerts a positive and statistically significant effect on Customer Satisfaction (β = 0.487; p < 0.05), while Service Quality also shows a positive and significant influence (β = 0.388; p < 0.05). In addition, the Goodness of Fit (GoF) value of 0.639 suggests that the proposed model possesses strong explanatory capability. Overall, these results emphasize that both emotional factors, represented by brand love, and functional aspects, reflected in service quality, are essential determinants in improving customer satisfaction in logistics services.